2017
DOI: 10.1007/s11356-017-9439-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of cation structure in the phytotoxicity of ionic liquids: growth inhibition and oxidative stress in spring barley and common radish

Abstract: The present study determines the influence of three ionic liquids (ILs) containing cations with diversified structure on the growth and development of spring barley seedlings and common radish leaves. Increasing amounts of 1-butyl-1-methylpyrrolidinium hexafluorophosphate [Pyrrol][PF6], 1-butyl-1-methylpiperidinium hexafluorophosphate [Piper][PF6], and 1-butyl-4-methylpyridinium hexafluorophosphate [Pyrid][PF6] were added to the soil on which both plants were cultivated. The results of this studies showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 76 publications
3
9
0
Order By: Relevance
“…An increase in POD activity was also observed over time ( Figure 2). The results were confirmed in the literature [30,34,37,41]. There was an increase in POD activity in plants in contact with ILs.…”
Section: Effects Of Ils On Antioxidant Enzymes Activitiessupporting
confidence: 88%
See 2 more Smart Citations
“…An increase in POD activity was also observed over time ( Figure 2). The results were confirmed in the literature [30,34,37,41]. There was an increase in POD activity in plants in contact with ILs.…”
Section: Effects Of Ils On Antioxidant Enzymes Activitiessupporting
confidence: 88%
“…However, if sugar beet shoots growing under drought conditions were also sprayed with humic acids, then they had an increase in MDA content. Biczak et al [30,41] further indicated that the effect of xenobiotics on the MDA content is dependent on the plant species on which these substances act. These authors observed that the same ionic liquids and quaternary ammonium salts cause changes in MDA content in spring barley seedlings, but they did not cause MDA accumulation in common radish leaves.…”
Section: Effect Of Ils On Mda and H 2 O 2 Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45][46][56][57][58][59][60][61][62][63][64][65][66][67][68] In addition, imidazolium-based ILs are also interesting as a medium for examining plant growth and germination. [69][70][71][72] Furthermore, Dimitrijević et al [73] reported and discussed novel phase diagrams for aqueous solutions of 1-alkyl-3-methylimidazolium-and 1-butyl-3-ethylimidazoliumbased ILs combined with phosphate-based salts, namely, K 3 PO 4 or K 2 HPO 4 . The anion influence on the ability to form aqueous biphasic system (ABS) was investigated for the IL with the same 1-butyl-3-methylimidazolium cation, [bmim + ], and various anions, for example salicylate, [SAL -], trifluoromethanesulfonate, [TFS -], dicyanamide, [DCA -], and chloride, [Cl -].…”
Section: Ionic Liquids As "Green" Engineering Liquidsmentioning
confidence: 99%
“…More recently, signicant efforts have been made to assess IL (eco)toxicity and biodegradability in order to avoid potential risks. [12][13][14][15] ILs toxicity has been assessed using diverse biological models, such as bacteria, 15 fungi, 16 invertebrates, 17 algae, 18 sh, 19 plants, 20 and cells. 21 ILs biodegradability has been evaluated using standardized assays approved by the Organization for Economic Cooperation and Development (OECD) and the International Organization for Standardization (ISO), such as the dissolved organic carbon die-away test (OECD 301A), closed-bottle test (OECD 301D), and CO 2 headspace test (ISO 14593).…”
Section: Introductionmentioning
confidence: 99%